The Effects of Refund Rates on Corporate Reputation: In the Context of the Airline Industry - Mu, Yinjie (2020)
With the spreading of the COVID-19 in the worldwide, how to survive this pandemic is becoming a trending topic. The travel bans and sharp reduction of the amounts of tourists caused the airline industry and even the whole tourism industry to fall into an unprecedented predicament. The objective of this research is to explore the effective approaches on crisis management to resist the negative impacts of the COVID-19 for the airlines and even the whole tourism industries. Specifically, this research is going to test from the customer perspective whether the refund rate can positively affect the corporate reputation via influencing customer satisfaction. A quantitative research method was applied in this empirical study. There were 292 participants from the United States have involved in this research through an online questionnaire. The linear regression model from Hayes’ (2013) PROCESS macro was used to test the hypotheses of this research. Moreover, the Cronbach’s alpha test, KMO test, and Bartlett’s test were employed to test the internal reliability and construct validity of the measures of this research. On the one hand, the results show the refund rate has a significant positive indirect effect on corporate reputation via influencing customer satisfaction. That means that adopting a higher refund rate could be seen as an effective method on crisis management by improving the corporate reputation under the COVID-19 for the airlines. On the other hand, the results also present the purchase frequency moderates the influence of refund rate on customer satisfaction. Key Words: Crisis Management; Refund Rate; Customer Satisfaction; Corporate Reputation